Double-dose hepatitis B vaccination in cirrhotic patients on a liver transplant waiting list - Bonazzi,Patricia R. (2008)
Development of immunity to hepatitis B virus in cirrhotic patients waiting for liver transplantation is highly desirable. Though a double-dose regimen is available, little is know about its effectiveness. We examined the efficacy of double-dose hepatitis B virus vaccination in cirrhotic patients waiting for liver transplantation. We studied 43 patients who were waiting for liver transplantation. They were vaccinated with three doses of 40 mg hepatitis B vaccine at 0, 1 and 6 months; the normal dose is 20 mg. Efficacy was measured based on seroconversion of anti-HBs. Global response to the primary vaccination scheme was 67.5% (29 patients). Forty-one per cent of responders had anti-HBs titers above 1,000 IU/mL. No factors were associated with response, based on multivariate analysis. The vaccination scheme of 40 mg at 0, 1 and 6 months was superior to conventional vaccination doses (20 mg) for cirrhotic patients on a waiting list for liver transplantation.